Identification of Place Theory in the Mutun Beach Tourism Area, Lampung - Pradivta, I Made Surya Putra; Persada, Citra (Journal of Architectural Design and Urbanism, 2024)
Abstract. Mutun Beach, located in the Padang Cermin District, Pesawaran Regency, Lampung Province, Indonesia, is one of the natural tourist attractions with great potential to increase the local revenue in Pesawaran due to its combination of white sand, clear sea water, and various exciting activities offered. However, a significant tourist decrease has occurred, especially during the COVID-19 pandemic. In addition, the presence of competing beach resort developers, poor road access, inadequate aesthetic design, and poor waste management are also reasons why Pantai Mutun is becoming less popular. The collaboration of the "Place" theory elements is applied to maintain the attraction of Pantai Mutun. This study uses a quantitative descriptive method with survey data processed into simple statistics such as percentages and averages to answer research questions and test hypotheses. The results show that the application of "place" theory elements at Pantai Mutun received an average score of 2.47, categorized as Poor. This condition indirectly affects the sustainability of Pantai Mutun, with the predicted gradual decrease in the number of visitors in the coming years until a critical point is reached where the sustainability of the tourist area becomes difficult to maintain. Recommendations include the consistent integration of "place" theory elements in every aspect of design and management, as well as increasing the involvement of the local community in the area's management to ensure sustainability and the relevance of the design to the local culture.